A new genus of therevine stiletto flies from South America (Diptera: Therevidae) - Irwin, Michael E.; Winterton, Shaun L. (Zootaxa, 2020)
A new genus of Therevidae (Dasythereva gen. n.) is described from Argentina and Chile and comprises two distinctive new species (Dasythereva penai sp. n., D. patagonia sp. n.) from sandy habitats. A key to genera of Neotropical Therevinae is included to accommodate the inclusion of this new genus.